Institute for Aegean Prehistory : Study Center for East Crete (INSTAP, 2006)
[Dt.:] Die Internetseite des amerikanischen Forschungszentrums in Pachia Ammos informiert über Einrichtungen, listet den Bestand der eigenen Bibliothek auf und stellt eine Liste weiterführender Links zu Projekten, Museen etc. zur Verfügung. - [Engl.:] The website of the American research center at Pachia Ammos informs about the institution. There are listed the contents of the library catalog and you can find a collection of links concerning projects, museums et cetera.